Leukocyte-Associated Immunoglobulin-like Receptor-1 is regulated in human myocardial infarction but its absence does not affect infarct size in mice. Issue 1 (December 2017) - Ellenbroek, Guilielmus; de Haan, Judith; van Klarenbosch, Bas; Brans, Maike; van de Weg, Sander; Smeets, Mirjam; de Jong, Sanne; Arslan, Fatih; Timmers, Leo; Goumans, Marie-José; Hoefer, Imo; Doevendans, Pieter; et al.
Abstract Heart failure after myocardial infarction (MI) depends on infarct size and adverse left ventricular (LV) remodelling, both influenced by the inflammatory response. Leukocyte-associated immunoglobulin-like receptor 1 (LAIR-1) is an inhibitory receptor of ITAM-dependent cell activation, present on almost all immune cells. We investigated regulation of LAIR-1 leukocyte expression after MI in patients and hypothesized that its absence in a mouse model of MI would increase infarct size and adverse remodelling. In patients, LAIR-1 expression was increased 3 days compared to 6 weeks after MI on circulating monocytes (24.8 ± 5.3 vs. 21.2 ± 5.1 MFI, p = 0.008) and neutrophils (12.9 ± 4.7 vs. 10.6 ± 3.1 MFI, p = 0.046). In WT and LAIR-1−/− mice, infarct size after ischemia-reperfusion injury was comparable (37.0 ± 14.5 in WT vs. 39.4 ± 12.2% of the area at risk in LAIR-1−/−, p = 0.63). Remodelling after permanent left coronary artery ligation did not differ between WT and LAIR-1−/− mice (end-diastolic volume 133.3 ± 19.3 vs. 132.1 ± 27.9 μL, p = 0.91 and end-systolic volume 112.1 ± 22.2 vs. 106.9 ± 33.5 μL, p = 0.68). Similarly, no differences were observed in inflammatory cell influx or fibrosis. In conclusion, LAIR-1 expression on monocytes and neutrophils is increased in the acute phase after MI in patients, but the absence of LAIR-1 in mice does not influence infarct size, inflammation, fibrosis or adverse cardiac remodelling.